Endoscopy innovations - Vanbiervliet, Geoffroy; Gonzalez, Jean-Michel; Barthet, Marc (Endoscopy, 2014)
Innovation everywhere for everybody – this is the way we can summarize the 2014 Digestive Disease Week, which was held in Chicago, Illinois, last May. Many sessions introduced new innovative materials and concepts. From the robot of the future to the simplest ideas, the congress was fertile and sometimes full of surprises. Abstracts representing significant progress and innovations in the field of digestive endoscopy are reviewed here.